Severe Behçet's disease equally affects both genders in Egyptian patients: A multicentre retrospective follow-up study - D.H.S. Attia; R.A. Abdel Noor (PAGEPress Publications, 2020)
Behçet's disease is a relapsing multisystemic disease. Its highest prevalence is seen along the Silk Road. While several studies reported gender disparities, others didn't. Scarce data are available about the Arabs and the gender differences detected in some ethnicities could not be applied to others. Our study aimed to detect gender differences among a cohort of adult Egyptian patients with Behçet's disease. Medical files of 255 adult patients diagnosed with Behçet's disease at the Rheumatology and Rehabilitation Department of Kasr Al-Aini Hospital, Cairo University and the Internal Medicine Department of Tanta University, between 2002 and 2018, were retrospectively reviewed. The demographic features, the cumulative clinical features, the use, if any, of an intravenous pulse of methylprednisolone and immunosuppressive/biological drugs, and the frequency of the cumulative damage to the different organ systems were described. The disease severity score was calculated as well. The study revealed a prominent male predominance; the male to female ratio was 6.7:1. Acne/pseudofolliculitis was more common in males (28.6% vs 13.2%, p=0.046); the same was observed regarding any vascular involvement and peripheral venous disease (36.3% vs 18.4%, p=0.03 and 30.4% vs 13.2%, p=0.03, respectively). On the other hand, encephalitis and cranial nerve lesions were more prevalent in females (15.8% vs 6%, p=0.03 and 10.5% vs 3.2%, p=0.04, respectively). Severe Behçet's disease equally affects Egyptian males and females. BD should not be considered a benign disease in Egyptian females. The same quality of medical care should be equally offered to both genders.